OECD economic outlook. May 2014 - Preliminary version (Paris, 2014)
"The OECD Economic Outlook is the OECD's twice-yearly analysis of the major economic trends and prospects for the next two years. The Outlook puts forward a consistent set of projections for output, employment, prices, fiscal and current account balances. Coverage is provided for all OECD member countries as well as for selected non-member countries. This issue includes a general assessment, chapters summarising developments and providing projections for each individual country, a special chapter on growth prospects and fiscal requirements over the long term and a statistical annex"